2020
DOI: 10.1186/s12302-020-00429-z
|View full text |Cite
|
Sign up to set email alerts
|

AEO-7 surfactant is “super toxic” and induces severe cardiac, liver and locomotion damage in zebrafish embryos

Abstract: Background Fatty alcohol polyoxyethylene ether-7 (AEO-7), a non-ionic surfactant, has recently been receiving extensive attention from the ocean pipeline industry for its ability to inhibit corrosion. However, the present lack of information concerning the potential environmental toxicity of AEO-7, especially towards aquatic organisms, is a major impediment to its wider application. Here, we assess potential adverse effects of AEO-7 on zebrafish embryos employing a variety of assays, including … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 75 publications
1
11
0
2
Order By: Relevance
“…The toxicity of NCEO n to zebra fish embryos decreased with the growth of the EO units, which was consistent with the toxicity of polyoxyethylene ether surfactants to aquatic animals (Al‐Asmakh et al, 2020; Mustapha & Bawa‐Allah, 2020). The LC 50 for zebra fish embryos varies from 5.98 to 7.04 mg/L for NCEO n , which were less toxic than NPEO 10 to zebra fish embryos (LC 50 = 4.84 mg/L), which confirmed that NCEO n is safer than NPEO 10 .…”
Section: Resultssupporting
confidence: 82%
“…The toxicity of NCEO n to zebra fish embryos decreased with the growth of the EO units, which was consistent with the toxicity of polyoxyethylene ether surfactants to aquatic animals (Al‐Asmakh et al, 2020; Mustapha & Bawa‐Allah, 2020). The LC 50 for zebra fish embryos varies from 5.98 to 7.04 mg/L for NCEO n , which were less toxic than NPEO 10 to zebra fish embryos (LC 50 = 4.84 mg/L), which confirmed that NCEO n is safer than NPEO 10 .…”
Section: Resultssupporting
confidence: 82%
“…immotile, opaque, or embryos with undetectable heartbeats) were excluded. Healthy embryos were incubated in six-well plates containing prepared concentrations of AEO-7 (.4, .8, 3.2, 6.4, 12.8, 25 μg/L), PTU-E3 (negative control), and DEAB (10 and 100 μM) (positive control) [10,12]. The survival rate of the embryos was assessed until 4-dpf.…”
Section: Acute Toxicity Analysismentioning
confidence: 99%
“…The median lethal concentration (LC 50 ) was calculated by fitting a sigmoidal curve to the data on mortality using the GraphPad Prism 8 software (version 8.2.1, San Diego, CA, USA), as previously described [21,25,26]. In addition, we used this curve to calculate the LC 10 , LC 20 and LC 50 at a statistical significance of 95% (P < .05) [12,27]. Moreover, we calculated the no observed effect concentration (NOEC), which is the highest concentration that does not cause a significant effect (P < 0.05) relative to the negative control (PTU-E3).…”
Section: Acute Toxicity Analysismentioning
confidence: 99%
See 2 more Smart Citations